Female Farmers’ Agricultural Information Needs and Food Production: A Case Study of Imbulpe ds Division in Sri Lanka - S.D. Dilini Rathnachandra; S.H. Pushpa Malkanthi (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego, 2021)
The study was conducted to find out female farmers’ agricultural information needs and their impact on food production, in the Imbulpe DS Division in Sri Lanka. Of the female farmers in the area, 238 were taken as the sample for the study from seven selected Grama Niladhari (GN) divisions in the area. Female farmers were selected by using a simple random sampling method from these purposively selected GN divisions. A pre-tested, interviewer-administered questionnaire survey was used as the primary data collection method from March to July 2019. Data analysis was done by using descriptive statistics and chi-square analysis. The result revealed that the majority (62.6%) of respondents were middle aged (40-59 years), married, and belonged to families with 4-5 members. Most respondents (64.3 %) had studied up to junior secondary education level. Their average farm land size is 0.84 acres and they have farming experience of about 15 years. Most of the respondents mentioned that they had obtained higher levels of information needs about improved crop varieties. In addition, female farmers reported that they moderately need information on application of agrochemicals, improved market systems and modern farming technologies. Extension agents and other female farmers act as their major sources of agricultural information and ICT equipment acts as the least important agricultural information source in this area. Moreover, there is a significant positive association between the agricultural information needs and food production. Therefore, providing necessary agricultural information and enhanced utilization of ICT tools for agricultural information sources, and encouraging female farmers to participate in farming societies will lead to enhanced food production in this area.